2020
DOI: 10.21203/rs.2.20845/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude of virologic failure and associated factors among adult patients on antiretroviral therapy at Debre Markos Referral Hospital, Northwest Ethiopia, 2018

Abstract: Background : Viral load monitoring is used as an important marker for diagnosing early treatment failure in patients with HIV infection/AIDS. Ethiopia has started targeted viral load monitoring recently. However, factors leading to virological failure are not well understood. The aim of this study is to assess magnitude of virologic failure and associated factors among adult patient on ART at Debre Markos Referral Hospital, North West Ethiopia. Methods : Cross sectional study was conducted on 304 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Nonadherence to antiretroviral drugs in adult ART clients on adherence-enhancement counseling was a predictor of virological failure. This finding is similar to studies conducted at Gondar University Referral Hospital, 6 Debre Markos Referral Hospital, 17 and Dessie and Woldia referral hospitals, 18 Ethiopia and Zimbabwe, 19 where subjects who had good adherence were more likely to achieve viral load suppression. Survival studies conducted in southwestern Uganda showed that virological failure rates were significantly higher among participants who reported adherence <90% than those who reported good adherence >95%.…”
Section: Discussionsupporting
confidence: 86%
“…Nonadherence to antiretroviral drugs in adult ART clients on adherence-enhancement counseling was a predictor of virological failure. This finding is similar to studies conducted at Gondar University Referral Hospital, 6 Debre Markos Referral Hospital, 17 and Dessie and Woldia referral hospitals, 18 Ethiopia and Zimbabwe, 19 where subjects who had good adherence were more likely to achieve viral load suppression. Survival studies conducted in southwestern Uganda showed that virological failure rates were significantly higher among participants who reported adherence <90% than those who reported good adherence >95%.…”
Section: Discussionsupporting
confidence: 86%
“…Patients who had history of HIV-TB co-infection were around two times more likely to fail first-line antiretroviral treatment when compared to patients who had no history of TB co-infection. Similarly studies conducted in India in 2016 [32], Gutu District, Zimbabwe by 2017 [14], Debre Markos Referral Hospital, North West Ethiopia in 2018 [35], showed that HIV-TB co-infection was independent determinant factors of treatment failure among adult patients on ART. The occurrence of tuberculosis during antiretroviral treatment has multiple effects including pills burden and drug-drug interaction which may lead to first-line treatment failure [36].…”
Section: Plos Onementioning
confidence: 86%
“…This is in line with the studies conducted in Ethiopia, Debre-Markos and Arba Minch. 42,43 Finally, the use of cotrimoxazole prophylaxis was significantly associated with virological failure. In this study, patients who did not receive cotrimoxazole prophylaxis were more than twice as likely to develop virological failure as compared to those who did cotrimoxazole prophylaxis.…”
Section: Discussionmentioning
confidence: 99%